Overview of consumer units and electric power consumption in brazilian regions in the period 2003 to 2013 - Kirchner, Rosane Maria; Edler, Marco Antônio Ribeiro; Uliana, Renan Somavilla; Forno, Andriele Costa Dal; Oliveira, Tarcisio Dorn de; Boaro, Joana Kirchner Benetti (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The electricity sector has a strategic role as a provider of an essential service to the population and propellant of economic development of the country. The supervision and regulation of the Brazilian electrical sector are conducted by the National Electric Energy Agency (ANEEL). This research is characterized as quantitative descriptive with information from the database of ANEEL. To this end, it aims to analyze the behavior of historical series of electric power consumption and the number of consumer units in the Brazilian regions during the period from 2003 to 2013. For data analysis there were used the descriptive statistics, linear regression, and correlation index numbers. With this study, it was possible to realize that energy consumption was increasing in the course of the years studied, with the exception of 2005 and 2006 for Brazil and for the Southeast region. Already in the number of consumer units this growth was constant. Also, there was a strong correlation between energy demand and the number of consumer units. When selected the last four years (2010 to 2013), it was observed the consumption and the consumer units according to Brazilian regions considering the consumer sectors, which are: Commercial, Services and Others; Own Consumption; Public Lighting; Industrial; Public authorities; Accommodation; Rural; Rural Farmer; Rural Irrigation; Public services (water, sewer and sanitation) and Public Service (electric traction). These occurred in most of them, an increase over the previous year. Therefore, with increasing demand for energy and the number of consumer units, the Country has a great challenge both for obtaining the energy as the development in a sustainable way.